PARTISIPASI WALI MURID DI SEKOLAH DASAR (SD) KUTTAB AL FATIH BANDAR LAMPUNG - DERMAWAN, OKI (Universitas Islam Negeri Raden Intan Lampung, 2016)
Oki DermawanFakultas Tarbiyah dan Keguruan IAIN Raden Intan Lampungokidermawan76@yahoo.co.id Abstract Participation of parents in the school should take place at all educational institutions in Indonesia, including in Islamic educational institutions located in Bandar Lampung. The purpose of this study is determine the condition of participation of parents at the school in Bandar Lampung, a case study in Kuttab al Fatih Elementary School Bandar Lampung. Knowing the forms of participation of parents in educate their children together with the school. and determine the factors supporting or inhibiting the participation of parents. This study using a qualitative approach with case study design. The subject of research are: parents, teachers, and school websites. Data collection techniques using observation, interviews, and documentation. Validity using triangulation checking and triangulation methods. Data analysis technique is interactive analysis by Miles and Hurberman. Based on the results of this research, the participation of parents in Kuttab al Fatih Elementary School Bandar Lampung are: parent monthly meeting and involved in several school activities. Parents have not been involved in make decisions about the school. Another form of parent participation is payment of a monthly school fee, also guiding the children at home through a module that has been set up by the school. Parental understanding of the importance of participating in educate the children is still not all parents are aware and have not become a necessity, it because not all parent are join the “Whatsapp” group that provide by the school. Keywords: Parents’ participation, education, elementary school